From clinic to screen: A narrative review of telehealth in pediatric chronic disease management: Telehealth in pediatric chronic disease - Shamsi, Atefeh (Journal of Digital Health, 2024)
Background: Telehealth integrates traditional hospitalization into modern healthcare by utilizing digital devices, especially for pediatric chronic diseases. This new approach has promoted convenient home care by providing individualized support to healthcare providers, children, and their fami lies to facilitate constant management of physiological follow-up, prevention of complication and cost-effective services. Objectives: This paper investigated the studies of Iranian telehealth concerning pediatric chronic diseases and aimed to explore the benefits and challenges of telehealth and provided recommendations to improve implementation. Methods: We identified fifteen relevant studies through comprehensive database searches. These studies were analyzed in terms of different types of pediatric chronic diseases and the characteristics, outcomes, benefits and challenges of telehealth. Results: Telehealth could potentially transform pediatric care by facilitating home-based, personalized assistance. It enabled continuous physiological follow-up, complication prevention, and cost-effective services that bridge the frequent face-to-face follow up gaps in healthcare. Telehealth studies identified technological, regulatory and infrastructure challenges as the direct factors that inhibit the growth of telehealth services. Conclusion: Telehealth integration to traditional care offered advantages, including enhanced access, personalized care and cost-effectiveness. However, it was crucial to overcome challenges of technology, regulation and infrastructure. Investing in telehealth enhancement and developing strategies to address these obstacles can significantly improve healthcare outcomes for children with chronic diseases and reshape pediatric care.